ANDROID-BASED-GAME AND BLENDED LEARNING IN CHEMISTRY: EFFECT ON STUDENTS’ SELF-EFFICACY AND ACHIEVEMENT - Fitriyana, Nur; Wiyarsi, Antuni; Ikhsan, Jaslin; Sugiyarto, Kristian Handoyo (Jurnal Cakrawala Pendidikan, 2020)
The 21st century learning system demands the use of technology in learning instruction. This research focuses on the comparison between the use of android-based-game and blended learning in the Chemistry subject on the hydrocarbon lesson toward students’ self-efficacy and achievement. A quasi-experiment with post-test only design was adopted in this research. A number of 143 eleventh graders from two public senior high schools in Purworejo Regency, Indonesia were selected in a cluster random sampling as the research sample. The sample was classified into three groups depending on the media used, i.e. android-based-game only on face-to-face learning (ABG-FTFL), blended learning only (BL), and both android-based-game and blended learning (ABG-BL). Self-Efficacy Scale (SES) was used to obtain the data of students’ self-efficacy while the hydrocarbon test was used to obtain students’ achievement. One-way Analysis of Variance, Kruskal Wallis test, and descriptive quantity technique were performed in the data analysis, and it is found that the use of these technologies has a significant effect on the students’ self-efficacy and achievement. The use of ABG-BL is better in improving students’ self-efficacy while BL is better in enhancing students’ achievement. Therefore, the use of android-based-game and blended learning can be emphasized as media in chemistry learning to gain better self-efficacy and achievement among students.